Geographic considerations for flights with Remotely Piloted Aircraft Systems in Costa Rica - Masís-Campos, Ramón (2022)
The purpose of the following work was to study and analyze the territorial regulations that currently exist in Costa Rica and that limit pilots of Remotely Piloted Aircraft System (RPAS) to fly in controlled airspace (airports, aerodromes, heliports), as well as prohibited spaces (La Reforma, Arenal Volcano), restricted spaces (Murciélago, Paso La Palma, Presidential House, Ministry of Security) or in urban areas of the country. In the same way, the factors that determine the performance of the aircraft and flight safety were studied, such as: the climatic conditions of Costa Rica, especially the elements: winds, rains, temperatures, extreme events and visibility. In addition to the magnetic interference for navigation products of solar storms, among other local disturbances. Likewise, this work pointed out the corresponding factors with visual obstacles on the ground (buildings, trees, fauna, among others). Finally, the resources available to RPAS pilots to make better decisions in their operations based on weather forecasting and aeronautical cartography for navigation were shown, as well as complementary resources such as applications for mobile devices.